2010
DOI: 10.1371/journal.pgen.1000921
|View full text |Cite
|
Sign up to set email alerts
|

A Microarray-Based Genetic Screen for Yeast Chronological Aging Factors

Abstract: Model organisms have played an important role in the elucidation of multiple genes and cellular processes that regulate aging. In this study we utilized the budding yeast, Saccharomyces cerevisiae, in a large-scale screen for genes that function in the regulation of chronological lifespan, which is defined by the number of days that non-dividing cells remain viable. A pooled collection of viable haploid gene deletion mutants, each tagged with unique identifying DNA “bar-code” sequences was chronologically aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
219
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(234 citation statements)
references
References 69 publications
12
219
1
2
Order By: Relevance
“…Similarly, PA28g deficiency promotes premature ageing in mice 56 . In yeast, a genetic screen searching for ageing factors identified multiple short-lived mutants with autophagy defects 57 . In C. elegans, decreased expression of several autophagic genes (atg1, atg7, atg12, bec1 and atg18) shortens its lifespan, supporting the role of autophagy in longevity 58,59 .…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%
“…Similarly, PA28g deficiency promotes premature ageing in mice 56 . In yeast, a genetic screen searching for ageing factors identified multiple short-lived mutants with autophagy defects 57 . In C. elegans, decreased expression of several autophagic genes (atg1, atg7, atg12, bec1 and atg18) shortens its lifespan, supporting the role of autophagy in longevity 58,59 .…”
Section: Loss Of Clearance Mechanisms As a Determinant Of Ageingmentioning
confidence: 99%
“…S3b). Notably, the rate of validation is considerably higher compared to screening assays that have used pooled yeast deletion strains (6–31% hits validated) (Fabrizio et al., 2010; Matecic et al., 2010). To directly compare the results obtained with the conventional single culture CLS assay and with our high‐throughput screen, we modeled a survival curve from the survival coefficients of the corresponding knockout strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a recent systematic study of replicative lifespan of most viable deletion strains revealed that translation, the SAGA complex, and the TCA cycle mediate longevity (McCormick et al., 2015). Several studies have aimed to estimate the stationary‐phase survival of single deletion mutants in parallel (Fabrizio et al., 2010; Garay et al., 2014; Gresham et al., 2011; Matecic et al., 2010; Powers et al., 2006), showing that autophagy, vacuolar protein sorting, regulation of translation, purine metabolism, chromatin remodeling, and the SWR1 complex are major determinants of longevity. However, we are still missing a direct comparison of the lifespan effects of such gene deletions under nutrient‐rich and restricted conditions that would allow to systematically address the mechanisms of longevity by dietary restriction.…”
Section: Introductionmentioning
confidence: 99%
“…5a, a highly significant enrichment for all treatments was found (Hypergeometric test, P-valueo9.99e-5). Further, we find that MTA's common predictions set is enriched with human orthologs of known lifespan-extending genes in yeast and Caenorhabditis elegans, collated from the SGD database and from the literature 28,[31][32][33]41 (Supplementary Data 4, Permutation test, empirical P-valueo0.02). Finally, a recently published study has examined the correlation between gene expression measured in mice livers and lifespan extension across different diet regimens 42 .…”
Section: Transformationmentioning
confidence: 99%
“…S4 for a detailed stoichiometric explanation underlying the eicosanoids metabolism prediction). MTA's predictions also include the inosine monophosphate biosynthesis pathway whose inhibition was previously found to extend the CLS of yeast via the allosteric regulation of phosphofructokinase 31 (see Supplementary Note 1 and Supplementary Methods).…”
Section: Transformationmentioning
confidence: 99%